[tex]2) \\
\sqrt{7+\sqrt{7} } \times \sqrt{\sqrt{14}+ \sqrt{7+\sqrt{7} }} \times \sqrt{\sqrt{14}- \sqrt{7+\sqrt{7} }} = \\ \\
=\sqrt{7+\sqrt{7} } \times \sqrt{\Big(\sqrt{14}+ \sqrt{7+\sqrt{7} }\Big) \times \Big(\sqrt{14}- \sqrt{7+\sqrt{7} }\Big)} = \\ \\
=\sqrt{7+\sqrt{7} } \times \sqrt{\Big(\sqrt{14}\Big)^2- \Big(\sqrt{7+\sqrt{7} }\Big)^2 } = \\ \\
=\sqrt{7+\sqrt{7} } \times \sqrt{14- (7+\sqrt{7}) } } = \\ \\
=\sqrt{7+\sqrt{7} } \times \sqrt{14- 7-\sqrt{7} } }=[/tex]
[tex]=\sqrt{7+\sqrt{7} } \times \sqrt{7-\sqrt{7} } }= \\ \\
=\sqrt{(7+\sqrt{7}) \times (7-\sqrt{7} }) }= \\ \\
=\sqrt{7^2-(\sqrt{7})^2}=\sqrt{49-7}= \boxed{\sqrt{42} } [/tex]